External Iliac Artery-Appendicular Fistula due to Antegrade Unusual Migration of K-Wire from Hip to Pelvis: An Unreported Complication - Nagmani Singh; Chakra Raj Pandey; Bhaskar Raj Pant; Uttam Krishna Shrestha; Biraj Bista (Case Reports in Orthopedics)
Background. K-wires are thought to be extremely safe implants and complications as a result of direct insertion or migration are very rare. Complications may be life-threatening in some instances where migration results in injury to vital organs. We report one such case where antegrade migration of K-wire from the hip resulted in injury to external iliac artery and formation of external iliac artery-appendicular fistula. No such complication due to migration has ever been reported in the literature. Case Description. A 15-year-old boy presented with lower abdominal pain, right lower limb swelling and pain, inability to walk, and rectal bleeding for 1 month after 2 K-wires had been inserted in his right hip joint for treatment of slipped capital femoral epiphysis the previous year. On investigation, he was diagnosed to have external iliac artery-appendicular fistula for which he was surgically treated. Clinical Relevance. Antegrade migration of K-wire from hip joint may lead to life-threatening injuries which can be minimized by bending the end of the K-wire, keeping the tip protruding outside the skin wherever possible and by early removal of K-wire once its purpose has been achieved.